2002
DOI: 10.1093/humrep/17.1.161
|View full text |Cite
|
Sign up to set email alerts
|

Developmental potential of human spermatogenic cells co-cultured with Sertoli cells

Abstract: Results suggest that meiosis and spermiogenesis can be resumed in vitro, with normal differentiated spermatids showing a low fertilization potential but regular rates of blastocyst formation. However, most of the embryos did not reach the morula stage and showed major sex chromosome abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
110
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(113 citation statements)
references
References 55 publications
3
110
0
Order By: Relevance
“…Wikstrom et al (2004) found that only 50% of the boys with KS had germ cells in their testes, indicating a severely impaired fertility potential even in the peripubertal period. Therefore, a potential strategy for infertility in patients with KS is cryopreservation of ejaculated spermatozoa or testicular tissue early in the patients' adolescence (Sousa et al, 2002;Ichioka et al, 2006). Our present study partially supported that age may affect sperm recovery from KS patients.…”
Section: Discussionsupporting
confidence: 78%
“…Wikstrom et al (2004) found that only 50% of the boys with KS had germ cells in their testes, indicating a severely impaired fertility potential even in the peripubertal period. Therefore, a potential strategy for infertility in patients with KS is cryopreservation of ejaculated spermatozoa or testicular tissue early in the patients' adolescence (Sousa et al, 2002;Ichioka et al, 2006). Our present study partially supported that age may affect sperm recovery from KS patients.…”
Section: Discussionsupporting
confidence: 78%
“…The observation of a high percentage of spermatozoa with an apparently normal chromosomal content (85.1%), almost as high as in the general population, 18 is of very good prognosis for this patient, since the selection of these cells for ICSI does not represent an increased risk for aneuploidies. However, selection of female embryos by PGD should be considered at genetic counselling.…”
Section: Discussionmentioning
confidence: 70%
“…21,22 In the present study, an abnormal segregation of the (Y;13) was found during meiosis I, as only 13.6% of the secondary spermatocytes showed a normal chromosome complement. In this situation, most of the abnormal secondary spermatocytes might become arrested and degenerated, 18 which explains why the large majority of the round spermatids were normal (70%), as were in consequence most of the sperm (85.1%). Results also evidenced unpaired chromosome centromeric signals in most (73.5%) of the diploid germ cells, thus suggesting that the majority of the cells might not overcome meiosis I, blocking and degenerating at the primary spermatocyte stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The requirement of glial cell line-derived neurotrophic factor (GDNF) was also reported for long-term in vitro culture of self-renewing SSCs [25,31]. Subsequently, coculturing of SSC on feeder layers (viz., Sertoli cells, STO cells and embryonic fibroblast cells) was exploited as an alternative [46][47][48]. Among the co-culturing system, Sertoli cells have been emerged as the most commonly used feeder layers [48].…”
Section: Discussionmentioning
confidence: 99%